Development of a novel sandwich immunoassay based on targeting recombinant Francisella outer membrane protein A for the diagnosis of tularemia - Jang, Jieun; Kwon, Do Hyung; Jang, Ju-Hong; Lee, Dong-Gwang; Chang, Seo-Hyuk; Jeon, Min-Young; Jeong, Young-Su; Song, Dong-Hyun; Min, Jeong-Ki; Park, Jong-Gil; Lee, Moo-Seung; Han, Baek-Soo; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionTularemia, caused by the bacterium Francisella tularensis, poses health risks to humans and can spread through a variety of routes. It has also been classified as a Tier 1 Select agent by the CDC, highlighting its potential as a bioterrorism agent. Moreover, it is difficult to diagnose in a timely fashion, owing to the non-specific nature of tularemia infections. Rapid, sensitive, and accurate detection methods are required to reduce mortality rates. We aimed to develop antibodies directed against the outer membrane protein A of F. tularensis (FopA) for rapid and accurate diagnosis of tularemia.MethodsWe used a baculovirus insect cell expression vector system to produce the FopA antigen and generate anti-FopA antibodies through immunization of BALB/c mice. We then employed hybridoma and phage display technologies to screen for antibodies that could recognize unique epitopes on FopA.ResultTwo monoclonal antibodies, 6B12 and 3C1, identified through phage display screening specifically bound to recombinant FopA in a dose-dependent manner. The binding affinity of the anti-FopA 6B12 and 3C1 antibodies was observed to have an equilibrium dissociation constant of 1.76 × 10-10 M and 1.32 × 10-9 M, respectively. These antibodies were used to develop a sandwich ELISA system for the diagnosis of tularemia. This assay was found to be highly specific and sensitive, with detection limits ranging from 0.062 ng/mL in PBS to 0.064 ng/mL in skim milk matrices.DiscussionOur findings demonstrate the feasibility of a novel diagnostic approach for detecting F. tularensis based on targeting FopA, as opposed to existing tests that target the bacterial lipopolysaccharide.